The pedagogical and educational character of the educational actions of the recreational-sports programs (Impetus, 2021)
This is a reflection of pedagogical and didactic nature of the educational activities of recreation-sports programs offered today in the country and that stems from the concern to make clear what makes the sport and recreation a formative stage in each of their practices. This problem is embodied in the presence of specialized programs approaches that can lead to forgetting the experience and sensitivity, negating other forms of relationships and generating an exclusive production needs, efficiency, organic and objectification of the body, in a society now claims bodily practices with a transformative approach that contributes to building a peaceful society. We intend to draw attention to the didactics and pedagogical concepts that accompanies such scenarios today and so encourage the emergence of new proposals necessary to continue building Physical Education.